SHM_120897_HST_3D Black Earthenware Bucket - Bonnevier, Helena; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a black earthenware bucket with a curved handle and a rounded base from the Swedish Middle Ages. The bucket was collected in Kalmar, Sweden and is currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=516

Link to Sök I Samlingarna

https://samlingar.shm.se/object/6D0AFCE5-378A-4ABE-96B2-5FE955F245A8
Keywords: 3D Model; Museum Object; Archaeology; Archaeology; Photogrammetry; Archaeology/history; History and archaeology; Dynamic Collections; Swedish Middle Ages; Slottsfjärden; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi